Qur’anic Therapeutic Spiritual Communication for Students Involved in Cyberbullying from Broken Home Families - Ahmad Bahrul Hikam; Ahmad Badruddin; Mohamad Zaenal Arifin; Amin, Muhammad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
This study explores the delivery of Qur’anic spiritual messages by Islamic Education teachers to students from broken home families who are either victims or perpetrators of cyberbullying. The aim is to foster awareness of the importance of ethical interaction on social media and to develop emotional, mental, and spiritual resilience. Employing a qualitative case study approach, the research involved four Islamic Education teachers, two homeroom teachers, and five students from broken home backgrounds. Data were collected through observation and interviews, and analyzed using data reduction, data display, verification, and conclusion drawing. The findings reveal that a broken home environment can trigger students to become both victims and perpetrators of cyberbullying. As victims, students are at risk of psychological, emotional, and mental distress. As perpetrators, they may experience moral degradation and diminished humanity. The study concludes that the harmful effects of cyberbullying on students from broken home families can be mitigated through the therapeutic stimulation of Qur’anic spiritual messages, focusing on moral conduct, life principles, repentance, patience, and positive thinking.